Menuju Nol Limbah: Eksplorasi Motif Pilihan Makanan dan Dampaknya terhadap Minimisasi Sisa Makanan oleh Konsumen Restoran - Syarif, Rahmat; Amalia, A Nurul Suci; Adnin M, Jannatul; Astuti, Widya (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: The study aims to examine the effect of food choice motives on consumers’ intention to avoid food waste in casual restaurants. Methods: This current study utilizes a quantitative approach with a Structural Equation Model (SEM) and through the perspective of planned behavior theory. Research Finding: It is found that 4 food choice motives have a positive and significant influence on consumers’ intention to avoid food waste in casual restaurants. Theoretical contribution/Originality: It is the first study in Indonesia examining the influence of food choice motives on consumers’ intention to avoid food waste in the casual restaurant (rumah makan) setting Practitioner/Policy implication: This research offers managerial implications that can be utilised by restaurants to develop environmentally friendly programs. Research limitation : It needs to include the context of online food delivery apps that facilitate consumers to buy food at restaurants and consume it at home.